A Combination Approach in Inhibiting Type 2 Diabetes-Related Enzymes Using Ecklonia radiata Fucoidan and Acarbose - Blessing Mabate; Chantal Désirée Daub; Samkelo Malgas; Adrienne Lesley Edkins; Brett Ivan Pletschke (MDPI AG, 2021)
Although there are chemotherapeutic efforts in place for Type 2 diabetes mellitus (T2DM), there is a need for novel strategies (including natural products) to manage T2DM. Fucoidan, a sulphated polysaccharide was extracted from Ecklonia radiata. The integrity of the fucoidan was confirmed by structural analysis techniques such as FT-IR, NMR and TGA. In addition, the fucoidan was chemically characterised and tested for cell toxicity. The fucoidan was investigated with regards to its potential to inhibit α-amylase and α-glucosidase. The fucoidan was not cytotoxic and inhibited α-glucosidase (IC50 19 µg/mL) more strongly than the standard commercial drug acarbose (IC50 332 µg/mL). However, the fucoidan lacked potency against α-amylase. On the other hand, acarbose was a more potent inhibitor of α-amylase (IC50 of 109 µg/mL) than α-glucosidase. Due to side effects associated with the use of acarbose, a combination approach using acarbose and fucoidan was investigated. The combination showed synergistic inhibition (>70%) of α-glucosidase compared to when the drugs were used alone. The medicinal implication of this synergism is that a regimen with a reduced acarbose dose may be used, thus minimising side effects to the patient, while achieving the desired therapeutic effect for managing T2DM.